Pagpasok sa eksena ang sinehan sa panitikan at pag-aaral ng piling sinehan sa Recto - Pascual, Chuckberry J. (Diliman, Quezon City University of the Philippines Press, 2016)
Homosexual behavior in movie theaters in Manila, Philippines.
Includes bibliographical references (pages 219-230) and index.
In Tagalog.
Keywords: Gay men -- Sexual behavior -- Philippines -- Manila; Motion picture theater etiquette -- Philippines -- Manila; Homosexuality and theater -- Philippines -- Manila